Assessment of heavy metals pollution and ecological risk in surface sediments in the Tam Giang - Cau Hai lagoon area, Thua Thien Hue Province - Nguyen, Thi Hue; Duong, Thi Lim; Dang, Tran Quan; Nguyen, Thi Lan Huong; Tran, Thu Thuy; Nguyen, Thi Huong Thuy; Trinh, Minh Trang; Pham, Thi Dung; Nguyen, Viet Cuong (Vietnam Journal of Marine Science and Technology, 2025)
The Tam Giang - Cau Hai lagoon system plays an important role in the economic development of the Thua Thien Hue area. In this project, the study and analysis of several heavy metals, such As, Cd, Pb, Zn, Hg, Cr, and Cu contained in the lagoon system were taken to assess pollution levels and ecological risk. Thirty-five sediment samples were collected in the research area in January 2024 (rainy season). Metals’ concentration was analyzed by (Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The assessment method is based on comparisons with the national technical regulation on sediment quality (QCVN 43:2017). It includes the geo-accumulation index (Igeo), enrichment factor (EF), pollution load index (PLI), and ecological risk index (RI). Results indicate the concentration of heavy metals were As (4.65); Cd (0.08); Pb (11.93); Zn (33.66); Hg (0.07); Cr (12,88) and Cu (4.97) mg/kg that within the allowed limits for surface water and brackish water sediments in QCVN 43:2017/BTNMT (national technical regulation on sediment quality). The geo-accumulation index (Igeo) for the heavy metals (As, Cd, Pb, Zn, Hg, Cr and Cu) confirmed that the sediment was not polluted. The enrichment factor (EF) proved that human activities are the primary source of increasing concentration of As, Cd, Hg, and Pb in sediment. Based on PLI, the pollution level of Tam Giang - Cau Hai lagoon is considered good, and the ecological risk (RI = 20.75) in the study area is low.